The Effect of Probiotic Doses in Biofloc Growth on Hematological and Histological Status of Catfish - Teotonio Gomes, Guilherme; Andayani, Sri Andayani; Yanuhar, Uun Yanuhar (Graduate School, Universitas Brawijaya, 2023)
Biofloc technology is one of the promising methods to overcome water quality problems in fish farming. This technology uses an environmentally friendly approach and does not harm cultivated organisms. The success of biofloc technology depends on the accuracy of determining probiotics and doses in the treatment. This study used petrofish commercial probiotics containing Lactobacillus heterochiochii, Bacillus sp., Nitrosomonas sp., and Saccharomyces cerevisiae, with a bacterial density of 1.2 x 106 CFU.mL-1. This study aimed to determine the suitable doses of probiotics for growing biofloc. Biofloc has a high content of protein. In the biofloc process, fish will consume the floc. It led to hematology status and intestine histology alteration that caused effects on fish growth. The method used in this study was an experimental method with a completely randomized design with four treatments. Each treatment will be repeated three times. The variable test was a difference of doses of probiotic P0 (0 L.L-1 water), P1 (1 L.L-1 water), P2 (1.5 L.L-1 water), and P3 (2 L.L-1 water). The observations on the value of hematological status showed erythrocytes in the P2 treatment was 2.9 x 1012.L-1 and P3 was 2.5 x 1012.L-1. It was categorized as a normal condition, while P0 and P1 (2.0 x 1012.L-1) were below normal values. The hemoglobin values of P2 (9.6 g.dL-1) and P3 (9.0 g.dL-1) were in accordance with normal values, while P0 (4.9 g.dL-1) and P1 (6.1 g.dL-1) were below normal. The hematocrit value in P2 was under the normal limit of 39%, while the treatments P0, P1, and P3 were below the normal limit. The leucocyte values in all treatments (P0, P1, P2, and P3) were above the normal (high) value, influenced by high stocking density. The best intestinal villi length was found in P2, which is 2431.42 µm; the villi width is 631.90 µm. Based on the observations on all variables, it can be stated that the probiotic doses have significant biofloc growth and hematological and histological intestine status. Furthermore, the (P2) treatment with 1.5 L.L-1 water effectively affected the growth of catfish (Clarias sp). Keywords: Biofloc, Catfish, Hematology, Histology, Probiotic Petrifish.